Assessment the Effect of Lactobacillus Acidophilus on Escherichia Coli Serotype O157:H7 with Detection of Some Virulence Factors - Mokhtar Jawad AL-Imam1 , May Talib Flayyih2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aim: To evaluation the effect of Lactobacillus acidophilus on Enterohemorrhagic Escherichia coli (EHEC)serotype O157:H7 with detection of some virulence factors.Methods: Two hundred and fifty specimens (stool) from children under five years for both sexes werecollected from some hospitals. All isolates were diagnosed according to morphological characteristics,biochemical tests. Monoplex pattern of PCR was used also for detection different genes in (7) Escherichiacoli )O157:H7 (isolates; include 16SrRNA, eae, lifA, Stx1,Stx2 that encoded for ribosomal RNA, intimin,lymphocyte inhibitory factor, shiga toxins. Three types of probiotics strains were obtained, Lactobacillusfermentum, Lactobacillus plantarum and Lactobacillus acidophilus (ATCC4356). Minimum inhibitoryconcentration (MIC) of cell free supernatants of Lactobacillus acidophilus was determined by employingdifferent dilutions (1/2, 1/4, 1/8, 1/16, 1/32), to detect the concentration of probiotic that will inhibit E.coli(O157:H7) growth.Results: Results showed, 210 (84%) samples were identified as E.coli from 250 samples. The result showed(7) isolates were identified as Enterohemorrhagic Escherichia coli (EHEC) serotype O157:H7 and showed allisolates of O157:H7 were positive for 16SrRNA gene with (213bp) and eae with (741bp), lifA with (712bp),only Stx1 gene appeared in all isolates with (446bp) and no bands with Stx2. Current result showed only cellfree culture supernatant of Lactobacillus acidophilus has inhibitory activity against all E.coli (O157:H7)isolates with different dilutions (1/2, 1/4, 1/8, 1/16, 1/32), while Lactobacillus fermentum, Lactobacillusplantarum have no effect against E.coli (O157:H7). The result showed the bacteriocin has inhibitory effectagainst E.coli (O157:H7), while organic acids and hydrogen peroxide haven’t any role in inhibition. The(MIC) value was (1/8) which inhibits the bacterial growth of isolates.